Promoting mental health through an inner city community arts programme: a narrative inquiry - Stickley, Theodore (2008)
The focus of this study is a community arts programme, Art in Mind, which is based in an inner-city area of an East Midlands city in the UK and was funded by the government's New Deal for the Communities. The aim of the qualitative research study was to gain understanding of the human processes involved in setting up such a project and to ascertain the subsequent benefits to participants. The research was conducted in two stages: stage one involved semi-structured interviews with seven of the original Art in Mind Steering Group members and stage two comprised interviews with eleven participants who were interviewed up to three times over a one-year period. Sixteen people were interviewed in total. The findings from participants are presented as a case-series. Interviewees included those who subsequently became members of the 'Lost Artists Club', one of the community-based activities that originated within the project and those who engaged with an 'Arts on Prescription' programme. In both stages, a total of 35 qualitative interviews were conducted.